Note on a class of k-paranormal weighted composition operators on the Fock space Fp(C) - Santhoshkumar, C.; Veluchamy, T. (Vysoké učení technické v Brně, Fakulta strojního inženýrství, Ústav matematiky, 2020)
In this paper, we characterize the k-paranormal, isometric, spectral radius and the numerical radius of the weighted composition operator C.